2010
DOI: 10.1590/s1676-06032010000200023
|View full text |Cite
|
Sign up to set email alerts
|

Deep-water Ophiuroidea (Echinodermata) from off Chile in the Eastern South Pacific

Abstract: The ophiuroids collected during the Oceanographic Expedition PUCK (SONNE-156) in 2001, in the framework of the project "Interactions between productivity and environment along the Chilean continental shelf" were analyzed. Eight samples had ophiuroids; Fifteen species were distributed in the following families: Gorgonocephalidae (2), Asteronychidae (2), Ophiomyxidae (1), Ophiacanthidae (2), Ophiuridae (5), Amphiuridae (1), and Ophiolepididae (2). Four species were recorded for the first time from Chilean waters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
1
9
0
2
Order By: Relevance
“…Based on Figure 5, higher PC1 scores correspond to proximal vertebrae that are shorter in length but higher in overall shape, and longer at the ventro-proximal, distal (Figure 4a). In addition, the distal vertebrae in A. loveni, widely reported as a prehensile species (Fujita & Ohta, 1988;Manso, 2010), are also similar to the proximal vertebrae of Ophiothrix savignyi (Figure 4a). This similarity in PC1 scores shows the morphological Each line color on the phylogenetic PCA plot c represents the following phylogenetic clades (order): Green, Amphilepidida; Blue, Ophiacanthida; Purple, Ophiurida; and Black, Euryalida middle groove (landmarks 17, 18, and 20).…”
Section: Re Sultssupporting
confidence: 53%
“…Based on Figure 5, higher PC1 scores correspond to proximal vertebrae that are shorter in length but higher in overall shape, and longer at the ventro-proximal, distal (Figure 4a). In addition, the distal vertebrae in A. loveni, widely reported as a prehensile species (Fujita & Ohta, 1988;Manso, 2010), are also similar to the proximal vertebrae of Ophiothrix savignyi (Figure 4a). This similarity in PC1 scores shows the morphological Each line color on the phylogenetic PCA plot c represents the following phylogenetic clades (order): Green, Amphilepidida; Blue, Ophiacanthida; Purple, Ophiurida; and Black, Euryalida middle groove (landmarks 17, 18, and 20).…”
Section: Re Sultssupporting
confidence: 53%
“…L. Clark, 1941;Djakonov, 1954;Chang et al, 1962Chang et al, , 1964A. M. Clark and Courtman-Stock, 1976;Baker, 1980;Paterson, 1985;Irimura, 1991;Liao and A. M. Clark, 1995;Fujita and Ohta, 1988;McKnight, 2000;Stöhr, 2005;Manso, 2010;Okanishi et al, 2011). On the other hand, Lineage 1 lacks mesh-like thickened skin, and external characters match with those of syntypes of A. loveni…”
Section: Systematicsmentioning
confidence: 99%
“…Recent surveys of the fish and invertebrate faunas of Guadalupe Island (Reyes Bonilla et al, 2009, 2010, have shown that many species present at Guadalupe Island also occur near the Baja California Peninsula, at similar or even lower latitudes than Guadalupe. From these observations we suggest that it is feasible that G. eucnemis also follows the mentioned pattern and it may have resident populations in deep waters somewhere close to the mainland.…”
Section: Discussionmentioning
confidence: 99%
“…There are 10 valid species of this genus distributed worldwide , three of which are present in the eastern Pacific: Gorgonocephalus diomedeae Lütken & Mortensen, 1899, only found in Panama (Lütken & Mortensen, 1899); Gorgonocephalus chilensis (Philippi, 1858) from Chile (Manso, 2010); and Gorgonocephalus eucnemis (Müller & Troschel, 1842). The latter is a boreal species resident of the Atlantic and Pacific Oceans; in the Pacific region it occurs in the East Siberian Sea, Laptev Sea, Chukchi Sea, Okhotsk Sea and Sea of Japan, and in the eastern margin it can be found from the Bering Sea to California, at depths from 8-1850 m (Hendler, 1996;Lambert & Austin, 2007).…”
Section: Introductionmentioning
confidence: 99%